Causes of Supply Chain Disruptions An Empirical Analysis in Cold Chains for Food and Pharmaceuticals - Brenner, Verena; SpringerLink (Online service) (Wiesbaden : Springer Fachmedien Wiesbaden : Imprint: Springer Gabler, 2015)
Verena Brenner provides a systematic approach for the investigation, measurement, and management of supply chain disruptions. A terminological, theoretical and practical basis for the analysis of supply chain disruptions is developed to create a consistent and transferable research framework. To better understand why certain supply chains are more susceptible to disruptions than others, this framework is then tested empirically in cold chain logistics. Based on a survey with approximately 60 supply chain specialists from production, distribution and retail of food and pharmaceuticals, drivers for resilience and vulnerability of supply chains are identified by comparing how partnerships and transactions were organized. Thereby, strategies for assuring the robustness of supply chains are depicted and connections to company-internal risk management are highlighted. Contents Measuring Disruptions in Supply Chains Analyzing Causes of Supply Chain Disruptions Challenges in Food and Pharmaceutical Logistics Evidence on Disruptions in Cold Chains Target Groups Researchers and students in the fields of logistics, supply chain management, and business administration Practitioners in the fields of logistics, quality management, and business continuity management The Author Dr. Verena Brenner completed her PhD at Jacob University Bremen gGmbH under the supervision of Professor Dr. Michael Hülsmann at the Faculty of International Logistics.
Measuring Disruptions in Supply Chains -- Analyzing Causes of Supply Chain Disruptions -- Challenges in Food and Pharmaceutical Logistics -- Evidence on Disruptions in Cold Chains.
Keywords: Economics; Industrial management; Operations research; Economics/Management Science; Production/Logistics/Supply Chain Management; Management/Business for Professionals; Operation Research/Decision Theory